2016
DOI: 10.1016/j.jcv.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Screening, characterisation and prevention of Hepatitis B virus (HBV) co-infection in HIV-positive children in South Africa

Abstract: BackgroundIn South Africa, the first HBV vaccine dose is administered at age 6 weeks, leaving a potential window for vertical transmission. Insights into HBV seroprevalence in the vulnerable HIV-infected group are important to drive improvements in surveillance, treatment and prevention.ObjectivesWe set out to implement a screening program for HBV among HIV-infected children and adolescents in Kimberley, South Africa. Our aims were to demonstrate that screening is feasible and sustainable, to establish the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
(15 reference statements)
1
29
0
Order By: Relevance
“…The mid‐point prevalence was 6.8% (IQR 2.5‐10.0). Prevalence ranged from 2% to 20% across six estimates from Nigeria and between 0% and 20.5% in South Africa . Extremely high prevalence (43%‐46%) was observed in Romania in two studies where HIV infection was acquired nosocomially prior to 1995.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mid‐point prevalence was 6.8% (IQR 2.5‐10.0). Prevalence ranged from 2% to 20% across six estimates from Nigeria and between 0% and 20.5% in South Africa . Extremely high prevalence (43%‐46%) was observed in Romania in two studies where HIV infection was acquired nosocomially prior to 1995.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence ranged from 2% to 20% across six estimates from Nigeria [37][38][39][40][41][42] and between 0% and 20.5% in South Africa. [43][44][45][46] Extremely high prevalence (43%-46%) was observed in Romania in two studies 47,48 where HIV infection was acquired nosocomially prior to 1995. A high prevalence (32.6%) was also found in Thailand among young people perinatally infected with HIV (mean age 14 years).…”
Section: Children and Young Peoplementioning
confidence: 99%
“…A previous study of HBV serology in adults in the same setting found HBsAg prevalence of 9.5% (55/579) (4). Children were recruited as part of the C o-infection in S outh- A frican C hildren (‘COSAC’) study as previously described (19,20). The lower age limit of recruitment was 6 months in order to limit the detection of maternal anti-HBs.…”
Section: Methodsmentioning
confidence: 99%
“…KReC children were confirmed HIV-negative in 163 cases (93.7%). A further 11 children did not have an HIV test result recorded, but were assumed to be HIV-negative based on the clinical data recorded at the time of admission to hospital. HIV-positive children were recruited primarily from HIV out-patient clinics between September 2009 and July 2016 as previously described (19,20). We recorded date of commencement of anti-retroviral therapy (ART), CD4+ T cell count and percentage, and HIV RNA viral load using the time point closest to the sample that was analysed for HBV serology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation